Achieving dual functions of texture modification and water retention of shrimp surimi products with the combination of epigallocatechin-3-gallate and γ-cyclodextrin. (30th August 2023) - Wang, Zonghan; Li, Deyang; Liu, Xiaoyang; Zhang, Min; Chu, Pengfei; Zhu, Beiwei; Liu, Donghong; Zhou, Dayong
Highlights: A feasible use strategy for EGCG is introduced and verified into surimi products. γ-CD/EGCG complex act as a texture modifier and water retainer in shrimp surimi. XPS and molecular docking are used in the regulation mechanism investigation. Encapsulated EGCG avoids excessive crosslinking of myofibrillar proteins. An encapsulation prior to use of EGCG give a higher phenolic retention in products. Abstract: Epigallocatechin-3-gallate (EGCG) exhibits excellent cross-linking effects of myofibrillar proteins, it is prone to self-aggregation, causing excessive cross-linking and moisture loss of gels, which limits its application as a food additive in surimi products. Here, through combination γ-cyclodextrin and EGCG into one inclusion complex, we achieved proper usage of EGCG in shrimp surimi products: elevating both water holding capability and texture properties (hardness, chewiness and resilience). Moreover, the mechanism behind excellent performance was elucidated: as texture modifiers, the complexes improved gel network integrity through intermolecular interactions and moderated disulfide bonds; and as water retainer agents, the complexes promoted transformation of nitrogen in proteins towards the form of protonated amino, facilitating the occurrence of hydration. Furthermore, the inclusion complexes brought a higher phenolic retention within products in contrast with direct addition of EGCG. This work may propose novel insights for the usage of polyphenols as additives in surimi-based products.